2004
DOI: 10.1103/physreva.70.032321
|View full text |Cite
|
Sign up to set email alerts
|

Optimal measurements for relative quantum information

Abstract: We provide optimal measurement schemes for estimating relative parameters of the quantum state of a pair of spin systems. We prove that the optimal measurements are joint measurements on the pair of systems, meaning that they cannot be achieved by local operations and classical communication. We also demonstrate that in the limit where one of the spins becomes macroscopic, our results reproduce those that are obtained by treating that spin as a classical reference direction.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
136
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(141 citation statements)
references
References 29 publications
4
136
0
Order By: Relevance
“…Indeed, the notion of entanglement is affected by the additional restrictions [7,8], and new protocols arise, e.g., perfect data hiding [9] becomes possible [7]. On the other hand, it has been shown [7,10] that the extra resource of a shared reference frame (i.e., a nonlocal state) allows to overcome the restrictions imposed by the SSR (note that [10] also adressed non-Abelian SSR); conversely, private reference frames restrict the possible operations of an eavesdropper and can thus be employed for cryptographic tasks [11].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the notion of entanglement is affected by the additional restrictions [7,8], and new protocols arise, e.g., perfect data hiding [9] becomes possible [7]. On the other hand, it has been shown [7,10] that the extra resource of a shared reference frame (i.e., a nonlocal state) allows to overcome the restrictions imposed by the SSR (note that [10] also adressed non-Abelian SSR); conversely, private reference frames restrict the possible operations of an eavesdropper and can thus be employed for cryptographic tasks [11].…”
Section: Introductionmentioning
confidence: 99%
“…Bartlett et al have shown that in the absence of a reference for spatial orientation the communication of classical and quantum information using spin particles is still possible provided the spins are entangled and the information is encoded in SSR-invariant subsystems [10]. They have also shown how a private shared reference for spatial orientation can be used for secret communications [11]. The effects of finite references has been studied in a variety of ways.…”
Section: Introductionmentioning
confidence: 99%
“…of secret bits that can be exchanged once a private SRF is established [6]. Such a tight balance provides a new understanding of reference frames as a communication resource.…”
mentioning
confidence: 99%
“…In fact, we can relate the above protocol with the cryptographic protocol of Ref. [6], where a private SRF is used to communicate a secret string of bits. While in our case we have asymptotically N qbits + 3 log N secret bits 鈭掆啋 private SRF , (10) in the case of Ref.…”
mentioning
confidence: 99%